Prime-O-glucosylcimifugin attenuates lipopolysaccharide-induced acute lung injury in mice - Chen, Na (Int Immunopharmacol, 2013)
Prime-O-glucosylcimifugin is an active chromone isolated from Saposhnikovia root which has been reported to have various activities, such as anti-convulsant, anticancer, anti-inflammatory properties. The purpose of this study was to evaluate the effect of prime-O-glucosylcimifugin on acute lung injury (ALI) induced by lipopolysaccharide in mice. BALB/c mice received intraperitoneal injection of Prime-O-glucosylcimifugin 1 h before intranasal instillation (i.n.) of lipopolysaccharide (LPS). Concentrations of tumor necrosis factor (TNF)-α, interleukin (IL)-1β and interleukin (IL)-6 in bronchoalveolar lavage fluid (BALF) were measured by enzyme-linked immunosorbent assay (ELISA). Pulmonary histological changes were evaluated by hematoxylin–eosin, myeloperoxidase (MPO) activity in the lung tissue and lung wet/dry weight ratios were observed. Furthermore, the mitogen-activated protein kinases (MAPK) signaling pathway activation and the phosphorylation of IκBα protein were determined by Western blot analysis. Prime-O-glucosylcimifugin showed promising anti-inflammatory effect by inhibiting the activation of MAPK and NF-κB signaling pathway.